Tangible : high touch visuals - Uleshka, ....-; Klanten, Robert, 1964- (Berlin : Gestalten, 2009)
Tangible presents graphic-inspired design, objects and orchestrated spaces by exceptional young creatives that are producing striking visual and spatial work. The borders between graphic design, illustration, art, interior design, architecture and craftsmanship are becoming increasingly blurred. More than ever before, graphic design is being used as the underlying medium together with multiple practices to manifest creative visions. Following in the footsteps of Hidden Track (2005) and Tactile (2007), Tangible presents further developments from the work of young designers and artists who are experimenting with this multidisciplinary approach and creating outstanding original tangible designs. These designers from different disciplines are choosing to no longer work exclusively in two dimensions, instead dealing intensively with space, materials and physical products. Each chapter in the book features different trends and styles demonstrating various approaches and solutions to this new area of graphic design. Graphics morph into spatial sculptures, the intangible is made visual through handmade craftsmanship, physical experiences, visual environments and staged spatial installations such as art installations, interiors and architecture as well as urban interventions. The striking visual work in Tangible indicates the rise of graphic-inspired interior designs as artists, graphic designers, typographers and illustrators transform their ideas into shops, restaurants, hotels and fair stand designs.
Keywords: Art, Modern -- 21st century -- Catalogs